2021
DOI: 10.3389/fmolb.2021.669664
|View full text |Cite
|
Sign up to set email alerts
|

Protein Aggregation as a Bacterial Strategy to Survive Antibiotic Treatment

Abstract: While protein aggregation is predominantly associated with loss of function and toxicity, it is also known to increase survival of bacteria under stressful conditions. Indeed, protein aggregation not only helps bacteria to cope with proteotoxic stresses like heat shocks or oxidative stress, but a growing number of studies suggest that it also improves survival during antibiotic treatment by inducing dormancy. A well-known example of dormant cells are persisters, which are transiently refractory to the action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 103 publications
(178 reference statements)
0
33
0
Order By: Relevance
“…In addition, persisters formed by the pore-forming HokB toxin were found to wake up based on pore disassembly via a combination of DsbC-mediated monomerization and DegQmediated peptide degradation, followed by membrane repolarization (Wilmaerts et al, 2019a). Furthermore, protein aggregate formation and removal were shown to be correlated with persister state entry and exit (Pu et al, 2019;Bollen et al, 2021;Dewachter et al, 2021). Based on these findings, we can infer that other persister formation pathways should be reverted to initiate persister state exit.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, persisters formed by the pore-forming HokB toxin were found to wake up based on pore disassembly via a combination of DsbC-mediated monomerization and DegQmediated peptide degradation, followed by membrane repolarization (Wilmaerts et al, 2019a). Furthermore, protein aggregate formation and removal were shown to be correlated with persister state entry and exit (Pu et al, 2019;Bollen et al, 2021;Dewachter et al, 2021). Based on these findings, we can infer that other persister formation pathways should be reverted to initiate persister state exit.…”
Section: Introductionmentioning
confidence: 87%
“…Protein aggregates in bacteria has been identified for many decades, but their functional role remains a debate (13,14). Protein aggregates in bacterial were initially considered as a collection of mis-folded proteins resulted from detrimental intrinsic or environmental stresses (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies showed that protein aggregates contribute to the asymmetric division of bacteria, and shape population heterogeneity which increases bacterial fitness (14,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent ATP depletion promotes protein aggregation, leading to increased lag time for cell resuscitation, correlated with the bacterial dormancy depth ( 17 ). Other phenotypes of dormant bacteria have been described, like the viable but non-culturable (VBNC) phenotype, in which cells remain viable, but in contrast to persisters, do not resume growth in medium on which they normally actively divide, unless specifically stimulated ( 13 , 19 21 ). Because of the similarities between persisters and VBNC cells, these phenotypes are described as part of a common dormancy continuum, in which VBNC cells represent the most dormant forms ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%